Decolonial Knowledge And Epistemic Resistance In Morocco - Tarik ElFalih (Pascasarjana IAIN Pontianak, 2026)
This paper undertakes a critical examination of the ways in which decolonial thought interrogates and reconfigures the production of knowledge within the Global South. It foregrounds the persistence of colonial structures and their formative influence on intellectual traditions, academic institutions, and dominant epistemological paradigms, as articulated by decolonial theorists. Particular attention is directed toward epistemologies emanating from the Global North, which frequently marginalize or efface local and Indigenous knowledge systems, thereby perpetuating a hierarchical order that privileges Western modes of thought. The analysis further engages with alternative epistemic practices that contest the hegemony of Eurocentric frameworks, drawing upon case studies from South Asia, Africa, and Latin America. These interventions encompass radical revisions of history and philosophy, the articulation of Indigenous pedagogies, and the preservation of oral traditions. Collectively, they advance perspectives that de-stabilize claims to the universality of Western epistemologies and open conceptual space for plural and situated forms of knowledge. By situating these interventions within the broader discourse of decolonial scholarship, this article demonstrates how knowledge can be reclaimed as an instrument of intellectual and political transformation, as well as a mode of resistance against enduring colonial logics in regions designated as the Global South.